Automated Behavioral Text Messaging and Face-to-Face Intervention for Parents of Overweight or Obese Preschool Children: Results From a Pilot Study - Militello, Lisa; Melnyk, Bernadette Mazurek; Hekler, Eric B; Small, Leigh; Jacobson, Diana (JMIR Publications, 2016)
BackgroundChildren are 5 times more likely to be overweight at the age of 12 years if they are overweight during the preschool period. ObjectiveThe purpose of this study was to establish the feasibility, acceptability, and preliminary effects of a cognitive behavioral intervention (TEXT2COPE) synergized with tailored mobile technology (mHealth) on the healthy lifestyle behaviors of parents of overweight and obese preschoolers delivered in a primary care setting. MethodsFifteen preschooler-parent dyads recruited through primary care clinics completed a manualized 7-week cognitive behavioral skills building intervention. Beck's Cognitive Theory guided the TEXT2COPE intervention content and Fogg's Behavior Model guided the implementation. The intervention employed a combination of face-to-face clinic visits and ecological momentary interventions using text messaging (short message service, SMS). To enhance the intervention's relevance to the family's needs, parents dictated the wording of the text messages and also were able to adapt the frequency and timing of delivery throughout program implementation. ResultsSelf-reported findings indicate that the program is feasible and acceptable in this population. The intervention showed preliminary effects with significant improvements on parental knowledge about nutrition (P=.001) and physical activity (P=.012) for their children, parental beliefs (P=.001) toward healthy lifestyles, and parental behaviors (P=.040) toward engaging in healthy lifestyle choices for their children. Effect sizes were medium to large for all variables. The timing, frequency, and wording of the text messages were tailored to the individual families, with 69% of parents (9/13) increasing the frequency of the tailored SMS from being sent once weekly to as many as 5 times a week. ConclusionsUtilizing a cognitive behavioral skills intervention with SMS has great potential for supporting clinical care of overweight and obese preschool children and their families. Further exploration of the potential effects on health and behavioral outcomes is warranted.